2001
DOI: 10.1097/00003072-200108000-00006
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG Uptake in a Patient with Psoriatic Arthritis

Abstract: The authors describe a patient with psoriatic arthritis in whom an increased level of F-18 fluorodeoxyglucose (F-18 FDG) uptake was seen in the joints of the hands. The areas of increased activity correlated well with the regions of symptoms reported by the patient. This case illustrates the potential use of F-18 FDG positron emission tomography to quantitatively assess the degree of arthritis activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Previous authors have suggested a good correlation between the symptoms of a patient with inflammatory joint disease and FDG uptake. 16 However, not all the joints showed concordant findings between clinical response and FIGURE 1. Coronal maximum intensity PET images of the hands of a 48-year-old female patient with an 11-month history of RA, showing increased FDG uptake in several metacarpophalangeal joints of both hands indicating synovial inflammation (A).…”
Section: Discussionmentioning
confidence: 98%
“…Previous authors have suggested a good correlation between the symptoms of a patient with inflammatory joint disease and FDG uptake. 16 However, not all the joints showed concordant findings between clinical response and FIGURE 1. Coronal maximum intensity PET images of the hands of a 48-year-old female patient with an 11-month history of RA, showing increased FDG uptake in several metacarpophalangeal joints of both hands indicating synovial inflammation (A).…”
Section: Discussionmentioning
confidence: 98%
“…This is slightly higher than the 71% achieved when using only the node size in the ANN as per CT interpretation criteria. This relative performance is in keeping with human observer interpretation accuracies, with FDG PET being superior to CT in the nodal status determination task (12)(13)(14)(15)(16)(17)(18)(19)(20). These node features can be used for interpretation Note.-This table was obtained by summing together the truth tables from each of 100 iterations of the ANN training and testing cycles.…”
Section: Discussionmentioning
confidence: 77%
“…Fluorine 18 fluorodeoxyglucose (FDG) positron emission tomography (PET) has been shown to be more accurate than CT in both staging of the mediastinum and detecting distant metastases (2,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and is increasingly incorporated into the clinical staging of NSCLC. Although its accuracy is much superior to that of CT in nodal staging, there still remains some overlap in the appearance of malignant and benign lymph nodes at FDG PET because (a) some inflammatory lymph nodes may have mild uptake of FDG and (b) small cancerous nodes may not appear very metabolically active (mildly FDG avid) owing to partial volume effects resulting from the limited reconstructed resolution of a PET scanner.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory arthropathies such as psoriasis [9] and rheumatoid arthritis [10] typically show FDG uptake when active (Fig. 3).…”
Section: Arthropathies and Degenerative Changementioning
confidence: 99%